Decreased blood pressure among community dwelling older adults following progressive muscle relaxation and music therapy (RESIK) - Niken Fitri Astuti; Etty Rekawati; Dwi Nurviyandari Kusuma Wati (BMC, 2019)
Abstract Background Hypertension is a major risk factor related to leading causes of death among older adults. Numerous efforts have been done but they still remain sub-optimal. This condition encourages development of a non-pharmacological therapy to complement pharmacological therapy, such as progressive muscle relaxation and music therapy (RESIK). The purpose of this study was to determine the effect of RESIK on blood pressure among older adults with hypertension in Depok Indonesia. Methods This study used quasi experimental design with pre and post test with control group approach. One-hundred older adults with hypertension were divided into two groups using stratified random sampling and purposive sampling. Result After 11 sessions of RESIK therapy in 6 days, the paired t-test showed a decrease in systolic blood pressure to 29.2 mmHg and a decrease in diastolic blood pressure to 16.2 mmHg. Conclusion In conclusion, RESIK decreased systolic blood pressure p < 0,001, but it did not significantly decrease diastolic blood pressure p > 0.167. It is recommended that RESIK be used regularly for an older adult population with hypertension.